Optimizing an adaptive fuzzy logic controller of a 3-DOF helicopter with a modified PSO algorithm - Naderi, Shokoufeh; Blondin, Maude J.; Rezaie, Behrooz (International journal of dynamics and control, 2023)
This paper investigates the controller optimization for a helicopter system with three degrees of freedom (3-DOF). The system is extensively nonlinear and highly sensitive to the controller’s parameters, making it a real challenge to study these parameters’ effects on the controller’s performance. We combined fuzzy logic with adaptive control theory to control the system and used metaheuristic algorithms to determine these parameters. Then, we compare the results with the controller optimized through the standard PSO and PID controller. The results indicate the high ability of MPSO to perform the global search and to find a reasonable search space. The proposed method’s effectiveness and robustness properties are shown through computer simulations, while the system is subject to uncertainties and disturbance. We also prove the efficiency of the MPSO algorithm by comparing it with the standard PSO and six other well-known metaheuristic algorithms and analyzing the results by statistical tests.